PENGARUH PEMBERIAN PERSENTASE TEPUNG DAUN GAMAL (Gliricidia sepium) DALAM RANSUM TERHADAP KARKAS BROILER - Ul Azmi, Dinda Aulia; Nilawati, Nilawati; Fati, Nelzi; Malvin, Toni (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2024)
This study aims to determine the effect of giving Gamal leaf flour and the best dose of giving Gamal leaf flour in the ration on broiler carcasses. The research was carried out experimentally with a Completely Randomized Design consisting of 4 treatments and 5 replications, each treatment consisting of 5 broilers. The treatments given consisted of control without giving Gamal leaf flour (A), giving 2% Gamal leaf flour (B), giving 4% Gamal leaf flour (C), and giving 6% Gamal leaf flour (D). Research parameters include carcass percentage, upper carcass percentage, and lower carcass percentage for broilers. The results of the research showed that the provision of Gamal leaf flour (Gliricidia sepium) was found to have a significant positive effect (p<0.05) on the percentage of the carcass, the percentage of the upper carcass, and the percentage of the lower carcass of broilers. The provision of gamal leaf flour (Gliricidia sepium) at a concentration of 2% gave the best results on broiler carcasses where the percentage of carcass was 69.978%, the percentage of upper carcass 44.41%, and the percentage of lower carcass 34.966%.